Exploring a Low-Carbon Development Path for Vietnam - Audinet, Pierre; Singh, Bipul; Kexel, Duane T.; Suphachalasai, Suphachol; Makumbe, Pedzi; Mayer, Kristy (Washington, DC: World Bank, 2015)
Bringing together a large set of data and building on two years of consultations in Vietnam with Government counterparts, research organizations, state-owned enterprises, the private sector, and the country’s international development partners, Exploring a Low-Carbon Development Path for Vietnam shows that achieving low-carbon development in Vietnam is both beneficial and feasible. To do so, this book delineates immediate and concrete policy guidance for the Government’s consideration to lower the country’s greenhouse gas emission trajectory. Based on a thorough data modeling effort, this book brings to light new data to formulate two scenarios that analyze Vietnam’s options up to the year 2030: a business-as-usual scenario and a low-carbon development scenario for the key carbon-emitting sectors of Vietnam. This book is unique in that it brings together and presents data on multiple sectors of Vietnam’s economy, making this information available for future reference. The effort is the result of collaboration with the Government of Vietnam as part of the Vietnam Low Carbon Options Assessment technical assistance. By highlighting several economic opportunities and clarifying the issues at hand, this work constitutes a milestone in this complex debate and should help all stakeholders tasked with designing the policies and measures to address the attendant challenges.